1963
DOI: 10.1016/s0022-4804(63)80009-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the hypoglycemic effect of insulin with systemic venous and portal venous administration

Abstract: Among the endocrinopathies, diabetes mellitus occupies a unique position. In Addison's d i s e a s e , hypothyroidism, hypoparathyroidism, hypopituitarism a n d o t h e r deficiency s t a t e s , there i s a clear correlation between a hormonal deficiency and the pathologic anatomy. In diab e t e s mellitus, however, t h i s i s not the c a s e . T h e pancreas may b e relatively normal from a morphologic point of view ' 0 l 7 except for minor changes which a r e thought by many t o b e due t o overstimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1969
1969
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…With regard to effects on glucose metabolism, the results of this study agree with those of many other authors (Weisberg et al, 1949;Gambasi et al, 1956;Galansino et al, 1958;Tarding & Schambye, 1958;Martin et al, 1959) that portal administration is less effective than peripheral in producing hypoglycaemia. It may be noted that with one exception (Martin et al, 1959) all these authors worked with anaesthetized animals, and anaesthesia can therefore be discounted as an explanation for the fact that certain other authors (Madison & Unger, 1958;Shoemaker et el., 1959;Starzl et al, 1962Starzl et al, , 1963Erwald et al, 1974) have reported that the site of administration had no significant influence on the hypoglycaemic response.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to effects on glucose metabolism, the results of this study agree with those of many other authors (Weisberg et al, 1949;Gambasi et al, 1956;Galansino et al, 1958;Tarding & Schambye, 1958;Martin et al, 1959) that portal administration is less effective than peripheral in producing hypoglycaemia. It may be noted that with one exception (Martin et al, 1959) all these authors worked with anaesthetized animals, and anaesthesia can therefore be discounted as an explanation for the fact that certain other authors (Madison & Unger, 1958;Shoemaker et el., 1959;Starzl et al, 1962Starzl et al, , 1963Erwald et al, 1974) have reported that the site of administration had no significant influence on the hypoglycaemic response.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these findings, other investigators (Reemtsma et al, 1963;Chaya et al, 1966) have not seen hypoglycaemia. In addition, Starzl et al (1963) were unable to demonstrate any significant difference in the hypoglycaemic response to prolonged insulin infusion between infusions given into the portal vein and into the systemic veins. As part of their experiments to determine the effect of portacaval transposition on carbohydrate metabolism Waddell and Sussman (1967) diverted the venous drainage of the normal dog's pancreas into the inferior vena cava, and following this procedure observed significantly reduced peripheral venous concentrations of insulin while glucose tolerance was increased.…”
Section: Discussionmentioning
confidence: 85%
“…It has been suggested that the continuing occurrence of the vascular complications of diabetes in spite of apparently adequate insulin injections may be related to absorption from the injection site being to systemic rather than to hepatic portal veins. Half or more of the insulin in portal blood is normally removed by the liver (Izzo et al, 1972), andStarzl et al (1975) have shown that this insulin may exert a hepatotrophic effect. A study was planned to compare glucose tolerance following systemic venous drainage of the pancreas with glucose tolerance in animals having portal venous drainage of the pancreas.…”
mentioning
confidence: 99%
“…Despite the above line of reasoning, previous studies have failed to demonstrate a clearcut advantage of portal over peripheral insulin delivery on carbohydrate metabolism. Portal insulin infusion, if anything, produces less hypoglycemia for a given dose than systemic insulin infusion (5,6,12,16). Peripheral insulin infusion with either a computer-controlled infusion device or a predetermined waveform results in the same glycemic excursion as portal insulin infusion (10,15,17,22).…”
Section: Discussionmentioning
confidence: 99%
“…At least in theory, portal insulin delivery may preferentially regulate hepatic glucose metabolism, whereas systemic insulin delivery may predominantly stimulate glucose uptake by peripheral tissues. However, despite its intuitive appeal, previous investigations have failed to show a clear-cut advantage of portal over peripheral insulin delivery (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%